Caspase-1-dependent pyroptosis of peripheral blood mononuclear cells predicts the development of sepsis in severe trauma patients: A prospective observational study. Issue 8 (February 2018) - Wang, Yu-chang; Liu, Qin-xin; Liu, Tao; Xu, Xi-e; Gao, Wei; Bai, Xiang-jun; Li, Zhan-fei
Abstract : Abstract: Pyroptosis plays a pivotal role in sepsis and septic shock in animal studies. However, its clinical significance in pathological conditions has not been well elucidated. This study aimed to evaluate the correlation between the percentage of pyroptotic peripheral blood mononuclear cells (PBMCs) and the clinical index and to investigate the relationship between PBMCs pyroptosis and the development of sepsis in trauma patients. This prospective study was conducted from October 2016 to May 2017 in a comprehensive trauma center. Sixty trauma patients and 10 healthy controls were enrolled. Peripheral blood samples were collected from the patients within 24 hours after injury. The percentages of pyroptotic and apoptotic PBMCs were measured using flow cytometry, and plasma levels of cytokines were evaluated using flow cytometric analysis with a human inflammation 13-plex panel. Trauma patients who developed sepsis had higher percentages of pyroptotic and apoptotic PBMCs at admission. Patients who developed sepsis (n = 33) had higher interleukin (IL)-6, IL-18, and monocyte chemotactic protein-1 (MCP-1) concentrations at admission than patients (n = 27) who did not develop sepsis. The percentage of PBMCs pyroptosis was significantly correlated with injury severity score (ISS), acute physiology and chronic health evaluation (APACHE) II score, IL-10, IL-18, and MCP-1 levels in trauma patients. PBMCs pyroptosis is a better biomarker in predicting the development of sepsis after trauma. This study indicates that the percentage of pyroptotic PBMCs increases during the early phase of trauma and that this increase is significantly correlated with the severity and state of inflammation in trauma patients. PBMCs pyroptosis is a potential marker for predicting the development of sepsis after trauma. Abstract : Supplemental Digital Content is available in the text